Leadership Experiences of Secondary School Principals in Leadership Experiences of Secondary School Principals in Trinidad and Tobago Trinidad and Tobago - Ramraj-Sookdeo, Asha (Walden University, 2020)
Meeting the leadership needs of principals poses a challenge globally. This problem is exaggerated in Trinidad and Tobago, as certification in leadership is not a requirement to become a principal. Additionally, the lack of empirical data about principal leadership in this country poses a major challenge in developing principals. The purpose of this transcendental phenomenological qualitative study was to explore principal leadership in secondary schools in this context. The conceptual lens incorporated Neumerski’s angle on instructional leadership theory developed from Hallinger’s model and Theoharis’s social justice leadership theory. The research questions addressed the nature of the principals’ leadership experiences in Trinidad and Tobago, focusing on how principals experience leadership to achieve their strategic goals and how they perceive their leadership development. Data collection involved Seidman’s 3-phase phenomenological interviews and the think aloud strategy from 10 secondary school principals selected from a stratified purposeful sample. Data analysis involved computer assisted qualitative data analysis software and manual phenomenological reduction techniques. Findings generated themes, leadership philosophies, context, diversity, marginalization, and social justice issues, along with power dynamics, principals’ dispositions, and evolution as leaders. The findings also revealed an achievement gap resulting from socioeconomic issues and a gap in principals’ understanding of social justice leadership theory. Implications for positive social change include developing principal leadership that can trigger strategic upgrades in schools’ leadership and governance structures that can promote quality and equity in the schools, the workplace, and this society.
Keywords: Secondary schools; Leadership experiences; School principals; Trinidad and Tobago